2011
DOI: 10.1097/md.0b013e3182079866
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Manifestations in Patients With Ankylosing Spondylitis

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disease of unknown origin affecting up to 1% of the population. Little is known about audiovestibular impairment in patients with AS, especially the presence of cochleovestibular dysfunction in these patients. To investigate audiovestibular manifestations in AS, we studied a series of 50 consecutive patients who fulfilled the modified New York diagnostic criteria for AS and 44 matched controls. Individuals with history of cardiovascular disease, cerebrovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…A tontura e a vertigem têm muitos fatores etiológicos (3,4,5,6,7). Diversos sinais da disfunção vestibular podem ser detectados por meio da anamnese, exame clínico, exame otoneurológico, além de exames que avaliam o sistema auditivo (8).…”
Section: Introductionunclassified
“…A tontura e a vertigem têm muitos fatores etiológicos (3,4,5,6,7). Diversos sinais da disfunção vestibular podem ser detectados por meio da anamnese, exame clínico, exame otoneurológico, além de exames que avaliam o sistema auditivo (8).…”
Section: Introductionunclassified
“…In the study by Amor-Dorado et al [5] , the incidence of abnormal results in vestibular tests was high. Erbek et al [8] determined vestibular pathology in 34% of the patients and statistically significant abnormal results in caloric tests.…”
Section: Discussionmentioning
confidence: 99%
“…Amor-Dorado et al [5] reported abnormal tympanometry results in 8% of the patients despite normal otomicroscopic examination and absence of any middle ear effusion. Amor-Dorado et al [5] explained this statement with the stiffness of the ossicular chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations